Oral administration of heat-inactivated Escherichia coli during suckling alleviated Salmonella typhimurium-derived intestinal injury after rat weaning - Cui, Minghui; Tang, Guangfu; Yan, Fang; Wang, Shunshan; Wang, Xi; Yao, Junhu; Xu, Xiurong (Frontiers in Immunology, 2023)
Newly weaned animals are susceptible to a wide range of microbial infections taking a high risk of developing post-weaning diarrhea. Trained immunity is the capacity of the innate immune system to produce a stronger and no-specific response against a secondary infection after a previous stimulation. The objective of this study was to evaluate if the heat-inactivated Escherichia coli (IEC) as an immunostimulant on suckling pups elicits a protective effect on the intestine of post-weaning rats challenged with Salmonella Typhimurium (S.Typhimurium), and we adapted a newborn rats model for this purpose. The results showed that oral administration of IEC during suckling alleviated the injury in ileal morphology induced by S.Typhimurium infection after weaning by expanding the levels of two tight junction proteins [zonula occluden-1 (ZO-1) and Occludin-1] and several secreted proteins (Lysozyme, Mucin-2, and SIgA) in the intestinal mucosa. Furthermore, the pre-stimulation with IEC significantly increased the expression of cytokines tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β) in an enhanced secondary reaction way after experiencing a resting period, and indicated the involvement of trained immunity. The 16S rDNA sequence results showed that pre-stimulation with IEC decreased the abundance of Clostridia, Prevotella, Christensenellaceae_R-7_group and Parabacteroides after intestinal infection of S.Typhimurium. Our results confirmed that the previous oral administration of IEC had a protective effect on intestinal injury in weaned rats infected with S.Typhimurium, via inducing an increased immune response, including enhanced inflammatory response and antimicrobial response capacity in the intestinal innate immune system. This study suggested a heterologous protective effect against bacterial pathogens within the concept of trained immunity, opening new avenues for further research with non-specific protection against intestinal infection.